Orientation-Dependent Nanomechanical Behavior of Pentaerythritol Tetranitrate as Probed by Multiple Nanoindentation Tip Geometries - Morgan C. Chamberlain; Alexandra C. Burch; Milovan Zečević; Virginia W. Manner; Marc J. Cawkwell; David F. Bahr (Crystals)
Nanoindentation can be leveraged to aid in the high fidelity modeling of dislocation mediated plasticity in pentaerythritol tetranitrate (PETN), an anisotropic energetic molecular crystal. Moreover, nanoindentation tip parameters such as tip geometry, size, and degree of acuity can be utilized to target anisotropic behavior. In this work, nanoindentation was conducted across a range of orientations on the (110) face of PETN to characterize resultant yield behavior, mechanical property measurements, and resultant slip behavior and fracture initiation. Three different indentation tips were utilized: a 3-sided pyramidal Berkovich tip, a 4-sided high aspect ratio Knoop tip, and a 90° conical tip. Ultimately, indenter tip radius was documented to impact yield behavior, whereas tip geometry affected larger scale processes such as slip, and tip acuity was the dominating factor that led to fracture. The axisymmetric conical tip, serving as a baseline, showed the least amount of variation in mechanical property measurements but also the largest distribution of maximum shear stress at which initial yielding occurred. Its high degree of acuity, however, was more prone to induce fracture at higher loads. The Knoop tip was shown to be suitable for average measurements, but also for elucidation of certain anisotropic features. A distinctly higher perceived hardness at 45° was measured with the Knoop tip, indicating less dislocation motion in that direction also observed in this work via scanning probe microscopy. Lastly, the commonly used Berkovich tip was a good compromise whereby it provided a representative volume element describing the average behavior of the material. These results can be utilized to target desired anisotropic behavior in a wider range of molecular crystals, as well as to inform theoretical considerations for dislocation mediated plasticity in PETN.